Decompose The Cognitive Mapping of The PISA Question’s Problem Solving Thinking Structure - Buhaerah, Buhaerah; Prayogo, Prayogo; Haq, Muhammad Ahsanul; Wahab, Wahab (Jurnal Pendidikan MIPA, 2023)
Abstract: The mistake in problem-solving indicates the presence of the cognitive structure parts, which are problematic. One of the causes is thinking structures that need to be better organized and connected or experience cognitive mistakes. This study aims to describe students' thinking structure mistakes in solving PISA questions and the efforts to correct these mistakes through defragmenting thinking structures. This study uses a qualitative approach. This study uses a qualitative approach, including data reduction, presentation, and conclusion. Based on the results of the study, the mistakes of the students' thinking structures in problem-solving to finish the PISA questions were experienced by all subjects, including students misunderstanding the problem, mistakes in devising a finishing plan, carrying out a finishing plan, and rechecking process. These mistakes are influenced by several reasons, including the need for literacy skills in reading the meaning of the questions, not focusing on essential instructions on the questions, mastery of understanding the concept of prerequisite material, mistakes in operating, and the structured and analysis errors. The defragmenting process is carried out to correct students' thinking structure mistakes in problem-solving through intervention processes including scaffolding-review, scaffolding-restructuring, scaffolding-explaining, cognitive conflict, and dis-equilibration. Keywords: defragmenting, problem, question, structure, solving, thinking Abstrak: Kesalahan dalam pemecahan masalah menunjukkan adanya bagian-bagian struktur kognitif yang bermasalah. Salah satu penyebabnya adalah struktur berpikir yang perlu ditata dan terhubung dengan baik atau mengalami kesalahan berpikir. Penelitian ini bertujuan untuk mendeskripsikan kesalahan struktur berpikir siswa dalam menyelesaikan soal PISA dan upaya memperbaiki kesalahan tersebut melalui defragmentasi struktur berpikir. Penelitian ini menggunakan pendekatan kualitatif. Adapun pendekatan kualitatif yang meliputi reduksi data, penyajian, dan penarikan kesimpulan. Berdasarkan hasil penelitian, kesalahan struktur berpikir siswa dalam pemecahan masalah hingga menyelesaikan soal PISA dialami oleh semua mata pelajaran, antara lain siswa salah memahami soal, kesalahan menyusun rencana penyelesaian, melaksanakan rencana penyelesaian, dan proses pengecekan ulang. Kesalahan tersebut dipengaruhi oleh beberapa hal, antara lain perlunya kemampuan literasi dalam membaca makna soal, tidak fokus pada petunjuk esensial soal, penguasaan pemahaman konsep materi prasyarat, kesalahan pengoperasian, serta kesalahan terstruktur dan analisis. Proses defragmenting dilakukan untuk memperbaiki kesalahan struktur berpikir siswa dalam pemecahan masalah melalui proses intervensi meliputi scaffolding-review, scaffolding-restructuring, scaffolding-explaining, kognitif konflik, dan dis-equilibration.  Kata kunci: defragmentasi, masalah, pertanyaan, struktur, pemecahan, pemikiranDOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp603-626